Donor derived HLA-G polymorphisms have a significant impact on acute rejection in kidney transplantation - Janssen, Maike (Human immunology, 2019)
Human leucocyte antigen G (HLA-G) is a non-classical HLA-class I antigen that exerts immunoregulatory functions. The polymorphisms 14-base pair (bp) insertion/deletion (ins/del) (rs1704) and +3142C>G (rs1063320) could modify the expression level of HLA-G. We genotyped 175 kidney recipients (41 with acute rejection and 134 without rejection) and additionally the corresponding donors for both polymorphisms in order to assess their impact on acute rejections one year after transplantation. In addition, we analyzed soluble HLA-G (sHLA-G) levels in sera of 32 living kidney donors and compared the sHLA-G levels in terms of the present genotype. In kidney transplant recipients we did not observe an impact of the 14-bp ins/ins and the +3142GG genotypes on acute rejection. In contrast, we found a higher frequency of these genotypes in the donors of the no-rejection collective compared to the rejection collective (4.9% vs. 24.6%; p=0.010; 9.8% vs. 31.3%; p=0.006). Soluble HLA-G levels were highest in healthy kidney donors homozygous for the 14-bp insertion. We conclude that the HLA-G polymorphisms of the donor are of importance for susceptibility of acute rejection in kidney transplantation. We suggest that the 14-bp ins/ins and the +3142GG genotypes are protective against kidney transplant rejection.
Gesehen am 16.07.2019